2003
DOI: 10.1165/rcmb.4892
|View full text |Cite
|
Sign up to set email alerts
|

C-Jun-NH2-Terminal Kinase Mediates Expression of Connective Tissue Growth Factor Induced by Transforming Growth Factor-β1 in Human Lung Fibroblasts

Abstract: Many of the fibrogenic effects of transforming growth factor-beta (TGF-beta) might be mediated by connective tissue growth factor (CTGF). The present study investigates the role of mitogen-activated protein (MAP) kinase in the expression of CTGF mRNA in the human lung fibroblast line, HFL-1. TGF-beta1 enhanced CTGF mRNA levels in a time- and concentration-dependent manner, and this enhancement was also dependent upon transcription. Inhibition of p38 MAP kinase or extracellular signal-regulated kinase (ERK) act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
68
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 39 publications
7
68
3
Order By: Relevance
“…Thus, the increased Smad2 activity and decreased c-Jun activity caused by JNK inhibition plays an agonistic role in TGF-␤ induction of CTGF expression in embryonic lung explants. This is different from what has been reported in mature lung fibroblasts (40).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, the increased Smad2 activity and decreased c-Jun activity caused by JNK inhibition plays an agonistic role in TGF-␤ induction of CTGF expression in embryonic lung explants. This is different from what has been reported in mature lung fibroblasts (40).…”
Section: Discussioncontrasting
confidence: 99%
“…This involves c-Jun binding to Smad2/3, blocking its interaction with the Smad element of the CTGF promoter (39). However, studies have also demonstrated that TGF-␤ activation of Smad2 and induction of CTGF in human lung fibroblasts is attenuated by JNK inhibition (40). Our previous studies have demonstrated that induction of CTGF expression by TGF-␤1 in embryonic lung explants is Smad-dependent (22).…”
Section: Discussionmentioning
confidence: 94%
“…This probably reflects an indirect effect of the reduction in TGF-␤1 mRNA levels. However, CC-401 may have inhibited the CTGF response in a direct manner because TGF-␤1-induced CTGF production in human lung fibroblasts is JNK dependent (19). The reduction in ␣-SMA ϩ myofibroblast accumulation that was seen with CC-401 treatment in the UUO model could operate via indirect or direct mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies suggest a role for JNK signaling in TGF-␤1 induced fibronectin production in fibro-blasts and in TGF-␤1 induced connective tissue growth factor (CTGF) production (18,19). However, a role for JNK signaling in tissue fibrosis has yet to be demonstrated clearly.…”
mentioning
confidence: 99%
“…ERK1/2 32-34 and JNK [35][36][37][38] are involved in fibrotic changes such as collagen synthesis and the induction of TGF-␤ and CTGF expression. To clarify the effect of ERK1/2 and JNK inhibition on the progression of fibrosis, we administered PD98059 and SP600125 in bleomycininduced fibrosis.…”
Section: Discussionmentioning
confidence: 99%